Interferência de plantas daninhas no desenvolvimento inicial de mudas meristemáticas de cana-de-açúcar - De Paula, Ricardo Jardim [UNESP] (2015)
New systems of sugarcane planting as PleneTM, Plene EvolveTM, Plene PBTM and AgMusaTM should get in the sugarcane area over next years, which will require specific initial weed interference studies. The objective of this study was to evaluate initial weed interference in planting of meristem seedlings (Plene EvolveTM). The weed species used was: Brachiaria decumbens, Ipomoea hederifolia, Digitaria horizontalis and Panicum maximum in four different densities (1, 2, 3 and 4 weed pot- 1), also had a control treatment free of weed interference, with a isolated study for each weed species. The statistical design was completely randomized with four replicates per treatment. The evaluations performed were: plant height at 45, 60 and 90 days after emergence (DAE), sugarcane tiller number count at 30, 60 and 90 DAE and the dry mass of both sugarcane and weeds at 90 DAE. Plant densities studied of I. hederifolia and D. horizontalis have not influenced negatively the early development of sugarcane plants planted by meristem seedlings. Otherwise, species of B. decumbens and P. maximum determined decreases in initial growth and development of sugarcane plants. Weed species of B. decumbens and P. maximum were more aggressive to sugarcane plants in its early development from meristem seedlings than I. hederifolia and D. horizontalis